Psychological Images Of Parents Against Mental Retardation Children In SLB Negeri 1 Bulukumba - Haerani; Nurlina; Sri Wahyuningsih (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Parents who have mentally retarded children will surely experience different challenges compared to those who have normal children. Parents whose children experience mental retardation usually get psychological pressure, resulting in stress and depression because parents feel lost hope for their children. The parents' emotional reactions immediately explode. The explosion of anger mixed with feelings of sadness, disappointment, frustration, pessimism, impatience, and shame. The purpose of this study was to determine the psychological description of parents of children with mental retardation in SLB Negeri 1 Bulukumba in 2018. The research method uses a descriptive design with a simple approach. The population in this study was 42 people. The research sample of 30 respondents. Data obtained through questionnaire sheets made by researchers to respondents. The results of this study showed that parents who experienced mild stress were 1 respondent (3.3%), moderate stress were 23 respondents (76.7%), while the level of severe stress was 6 respondents (20.0%). Then those with high coping are 27 respondents, and low coping is 3 respondents (10%). The conclusion from this study found that more parents experience moderate stress than mild and severe stress. Then, more parents have high coping than low coping.